Treatment Preferences in Young Adults with Moderate to Severe Psoriasis: A Qualitative Study from the Nordic Countries - Balieva Flora Nicol; Catton Louise; Claréus Birgitta W.; Danielsen Kjersti; Fierens Frederik; Iversen Lars; Koulu Leena; Osmanecevic Amra; Pasternack Rafael; Skov Lone (ADIS INT LTD, 2025)
Introduction The purpose of this study is to explore treatment preferences and identify patient characteristics in young bio-naive adults with moderate to severe psoriasis in the Nordic countries (Norway, Finland, Sweden, and Denmark).
Methods Patients were 18-45 years old and bio-naive but referred for biologic treatment of moderate to severe psoriasis. Patients were included at eight Nordic dermatology clinics. Patients with significant comorbidity or psoriatic arthritis were excluded. The Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI) were assessed along with basic patient information. A semistructured interview guide was used in individual qualitative interviews, asking patients about their treatment preferences and reasons, disease journey, and disease management. The interviews were analyzed using thematic content analysis. Twenty-four patients sufficed to reach saturation in this qualitative study.
Results The patient sample characteristics represented a qualitative variation in age, sex, symptoms, duration of disease, and country. We included a total of 12 male and 12 female patients. The mean age was 34 years (range 18-45 years), the mean age at diagnosis was 20 years (range 6-34 years), the mean & PLUSMN; standard deviation (SD) time since diagnosis was 13 & PLUSMN; 8 years, PASI was 9.5 & PLUSMN; 4.7, and DLQI was 15.2 & PLUSMN; 6.4.Interviews suggested that both the burden of disease as well as the burden of treatment influenced patient preferences regarding treatment attributes, hence getting alleviation from symptoms did not alone influence patient preferences. Time, effort, and inconvenience related to psoriasis treatments also influenced patient preferences.
Conclusions This first in-depth, qualitative study in young bio-naive adults with psoriasis suggests that patient preferences are focusing not only on symptom relief but also on alleviating the burden of psoriasis treatment. Understanding the reasons for patient preferences and the perspectives of young adults is needed to guide individual shared decision-making in psoriasis management.
Plain Language Summary Not much research has been done on understanding the disease burden and treatment needs of young adults suffering from psoriasis. This is an interview study with young adults from Nordic countries suffering from moderate to severe psoriasis with an active lifestyle. The adult patients were all referred for biologic treatment of psoriasis but had not yet started treatment when they were interviewed. The aim was to explore treatment preferences in this group.The study showed that treatment goals depended upon both alleviation of symptoms and obtaining a low treatment burden. The most influential symptoms were scaling, itching, and visible plaques. The most important treatment burden features were efficacy, durability, speed of response, safety, and convenience. Understanding the reasons behind these different treatment preferences is essential to help shared-decision psoriasis management that matches individual needs.